PROMOSI JAJANAN TRADISIONAL DUMBLEG KHAS GONDANG, NGANJUK DENGAN MEMANFAATKAN MEDIA SOSIAL: - LINA ROUDLOTUL JANNAH ALI MUKTI; Pawana Nur Indah; Indra Tjahaja Amir (JURNAL AGRIBISNIS, 2021)
Social media today is a technology that is connected to the internet, there are many benefits, and now often used by the various micro-market, small or medium units for the goal marketing strategies, especially as a promotion. But unfortunately, until now, social media has not been used by all micro-market places, UMKM (micro traditional market) dumbleg as traditional food in Gondang, Nganjuk. So research is needed on the use of social media as, a means of promoting traditional dumbleg food for consideration strategies of dumbleg producers. The purpose of this study was to 1) analyze the benefits of social media as a means of promotion for producers and consumers of dumblegs traditional food, and 2) to analyze the relationship between social media and the number of dumblegs purchased. The method used is descriptive quantitative with interviews with producers and consumers of dumbleg traditional food, and d ta analysis to determine the relationship between social media and the number of purchases using the chi-square. Research results 1) social media as a means of promotion is very useful for producers and consumers of traditional dumbleg foods, and 2) there is a relation between social media as a means of promotion with the number of purchases of dumbleg traditional food, as evidenced by the results of the chi-square analysis X2 count is greater than X2 table (13.459>12.592) or the sygn value. 0.036<0.05. Keywords: Dumbleg, Promotion, Benefits, Social Media